Mechanical properties of nickel nitrides under high pressures - Sagatov, Nursultan; Sagatova, Dinara (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2024)
The mechanical properties of previously known nickel nitrides, Ni6N-R-3, Ni3N-P6322, Ni3N-Cmcm, and Ni7N3-Pbca, were calculated from first principles using density functional theory at various pressures. Considered nickel nitrides are mechanically stable in the entire considered pressure ranges. It was shown that all phases are ductile and have low Vickers hardness values which are below the minimal criteria of hard materials, HV > 20 GPa. In addition, the fracture toughness was estimated.